1988
DOI: 10.1007/bf02596120
|View full text |Cite
|
Sign up to set email alerts
|

Does physician uncertainty affect patient satisfaction?

Abstract: Physicians may choose one of several strategies when initially uncertain about making a specific therapeutic recommendation. The authors investigated how patients' satisfaction is affected by disclosure of uncertainty and its attempted resolution during a clinical encounter. Three hundred and four patients awaiting appointments at a university hospital's ambulatory medical clinic were randomized to view one of five videotapes (VTs) of a patient seeking advice about antimicrobial prophylaxis for a heart murmur.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
0
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 16 publications
6
87
0
1
Order By: Relevance
“…Physicians are often concerned that acknowledging uncertainty to patients may undermine patient trust and satisfaction. However, some research has shown that patient satisfaction is affected by the manner in which the physician handles uncertainty, not whether or not he or she presents uncertainty, 99 consistent with previous theories. 100 When physicians are comfortable with uncertainty and collaborate with their patients in their medical care, patient trust and satisfaction are actually high.…”
Section: Individual Differences In Patient Responses To Uncertaintysupporting
confidence: 81%
“…Physicians are often concerned that acknowledging uncertainty to patients may undermine patient trust and satisfaction. However, some research has shown that patient satisfaction is affected by the manner in which the physician handles uncertainty, not whether or not he or she presents uncertainty, 99 consistent with previous theories. 100 When physicians are comfortable with uncertainty and collaborate with their patients in their medical care, patient trust and satisfaction are actually high.…”
Section: Individual Differences In Patient Responses To Uncertaintysupporting
confidence: 81%
“…28 Active participation would involve discussions of uncertainty and alternatives. Some existing studies suggest that when providers express uncertainty during medical encounters, patients are less satisfied and confident in their provider, [29][30][31] but these studies mostly examined scenarios in which providers indicated that they were unsure about proper treatments. Patient reactions to discussions of medical uncertainty require additional investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Although uncommon, physicians' expressions of uncertainty ("I don't know...") were not associated with lower patient ratings of the physician, in contrast to survey and vignette studies which suggest otherwise. 51,52 Concern has been raised about the inappropriate use of reassurance without adequate biomedical explanations or lack of empathic responses when patients present with MUS. 5,6 However, even accounting for the increased number of prompts in the MUS role, we found that physicians used empathy at least as frequently in the MUS role compared with the more straightforward GERD presentation, did not attempt to reassure more often, explored psychosocial domains, and admitted uncertainty more often.…”
Section: Discussionmentioning
confidence: 99%